Dry zone forests of Fiji: species composition, life history traits, and conservation - Keppel, Gunnar; Tuiwawa, M. (Taylor & Francis Australasia, 2007)
Species composition and life history traits of trees in native forests in the dry zone of Fiji were investigated. Areas receiving less than 2500 mm yr-1of rain and covered with native forest were identified using maps, aerial photographs, estimated climate (WorldClim), and field reconaissance. Ten forest remnants were identified and species lists and data on natural history and disturbance were compiled. Cluster analysis and DECORANA identified two principal forest types, moist forest (MF) and tropical dry forest (TDF), each defined by unique climate, species composition, and tree life history characteristics. TDF (reported for the first time from Fiji) has a pronounced dry season (5 consecutive months with < 100 mm rainfall each) and several deciduous canopy species. MF lacks a pronounced dry season and has few deciduous species. The amount and variability of rainfall seem to influence the type of forest in a particular location and disturbance is negatively correlated with precipitation. TDF are probably Fiji's most endangered ecosystems